Analysis of Factors Affecting Work Productivity - Rupiwardani, Irfany; Sari, Devita; Wahyuni, Ike Dian (Indonesian Journal of Global Health Research, 2024)
Subur Makmur Istana Embroidery Malang is one of the non-formal businesses or MSMEs in Malang City in the field of convection, with the main product being mukena or embroidered clothes. The aim of this research is to analyze the factors that influence work productivity. The sampling technique used was total sampling with a sample size of 35 workers. Cross sectional research design, statistical analysis using logistic regression tests. The research instruments used in this study were questionnaires, observation sheets, fatigue instruments using Subjective feelings of fatigue from the Japan Industrial Fatigue Research Committee (IFRC). Measurement of the physical work environment using a luxmeter for light measurement, and a sound level meter to measure noise. The research results show that there is a significant influence between age, work fatigue, motivation, length of service, lighting, and wages on work productivity. Meanwhile, the noise variable has no effect on work productivity, because for workers the noise generated by sewing, embroidery and cutting machines is considered not to disturb them while working.